Role of osteopontin in lung cancer evolution and heterogeneity. (April 2017) - Shi, Lin; Wang, Xiangdong
Abstract: Patients with lung cancer still have high mortality, recurrence rate after adjuvant treatment, and poor five-year survival rates, despite of advances in multidisciplinary anti-cancer therapies, e.g. chemotherapy, radiotherapy and targeted therapies, It depends upon the presence of intratumoral heterogeneity and complexity of lung cancer. There is growing evidence to suggest that osteopontin (OPN) may play a critical role in tumor progression and metastasis. The present review briefly describes the structure and molecular biology of OPN, highlights the role of OPN in the development and metastasis of lung cancer, and summarizes potential mechanisms of OPN heterogeneity in tumor to underline some of these inconsistencies. The article will emphasize the importance to understand the role of OPN in cancer evolution and heterogeneity and explore the potential of OPN as a therapeutic target.